Multiscale damage modelling of 3D woven composites under static and impact loads - Shah, S.Z.H. (Elsevier Ltd, 2021)
A multiscale progressive damage modelling methodology for 3-dimensional (3D) woven composites is presented. The proposed methodology is generic and can be implemented in most finite element software to create a digital twin for simulation of damage response. It uses 3D solid element (reduced integration) representation of the part for global analysis, while the local damage response, as well as matrix nonlinearity is modelled using a mesoscale constitutive unit-cell model of 3D woven composite consisting of idealised regions of polymer matrix and impregnated yarns. The idealised unit-cell model is defined based on realistic input from X-ray tomography of the 3D woven composite part and the micro-level constituent properties of the matrix and fibres. The damage model has been validated using quasi-static tensile/compression tests as well as dynamic drop-weight impact tests for both thermoset (epoxy) and thermoplastic (Elium) 3D woven composites. These simulations successfully demonstrate the accuracy and efficiency of the model for both 3D-textile composites. Â© 2021 Elsevier Ltd